CD133 expression in cancer cells predicts poor prognosis of non-mucin producing intrahepatic cholangiocarcinoma - Cai, Xiao Bo; Yuan, Xiaodong; Dooley, Steven; Weng, Honglei (Journal of translational medicine, 2018)
CD133 is a marker of stem cells as well cancer stem cells. This study investigated the association between CD133 expression in cancer cells and the clinical outcome of non-mucin producing intrahepatic cholangiocarcinoma (ICC).